Features of the power-law fluid over cylinders in a channel via gap aspects: Galerkin finite element method (GFEM)-based study - Faraz, Naeem; Majeed, Afraz Hussain; Mehmood, Asif; Sajad, Haseeba; Khan, Y. (Frontiers in Physics, 2023)
The purpose of this study is to conduct an exhaustive study of hydrodynamic forces, taking into account power law fluid flow over cylinders and presence gap aspects. The discretization of the two-dimensional system of non-linear partial differential equations was accomplished with the help of the GFEM. The research is carried out with a significance variance of flow behavior index (n) from 0.3 to 1.7, gap aspects (G_p) from 0 .0 to 0.3, and fixed Reynolds number (Re) 20, respectively. In order to obtain a solution that is extremely accurate, first a coarse hybrid computational mesh needs to be developed, and then more refinement must take place. The selection of the best possible case can be determined by comparing flow patterns, coefficients of drag and lift, and cylinder gaps. The drag characteristics are significantly more affected by the shear-thickening behavior than they are by the Newtonian or the shear-thinning behavior of fluids. Additionally, the shear-thickening behavior induces the drag coefficient to rise on the upstream obstacle as the gap spacing becomes more widespread.